Genome integrity relies on rapid recycling of DNA Pol III in bacteria - José Pablo Rascón Pérez; Ophélie d’Udekem d’Acoz; Nicolas Soubry; Wencheng Xu; Baljyot Singh Parmar; Stephanie C. Weber; Rodrigo Reyes-Lamothe (Proceedings of the National Academy of Sciences, 2025)
DNA replication requires precise coordination between DNA unwinding and DNA synthesis. In all domains of life, protein–protein interactions at the replisome maintain proximity between the enzymes that catalyze these two activities. Surprisingly, in bacteria, the replicative DNA polymerase (Pol III), responsible for DNA synthesis, is exchanged every few seconds. How processive synthesis is maintained under these conditions has remained unclear. Here, we use single-molecule microscopy in live cells to show that Pol III rapidly rebinds the replisome within seconds of dissociation. This fast recruitment is driven by an interaction with single-stranded DNA–binding protein (SSB), which enhances Pol III target search efficiency by ~20-fold. Disrupting this mechanism alters replisome stoichiometry, causes single-stranded DNA (ssDNA) accumulation, depletes free SSB, and leads to helicase disassembly and DNA breakage, culminating in genome instability. Our findings reveal a mechanism by which fast polymerase recycling sustains continuous DNA replication and genome integrity.